Dans le mouvement étudiant à McGill - Lévesque, Andrée (Madeleine Parent, militante, 2003)
Keywords: Mouvement étudiant; Parent; Madeleine; Université McGill; Étudiants

La formation académique des étudiants de premier cycle en psychologie à l'Université de Montréal: aspects situationnels, contextuels et globaux - Cagiotti, Isabelle (Université de Montréal, 2003)
Keywords: Psychologie; Université de Montréal; Étudiants

Attracting Foreign Students: The Case of Two Universities in Québec - Racine, Nicolas; Villeneuve, Paul Y.; Thériault, Marius (Journal of Studies in International Education, 2003)
A number of factors may influence the recruitment of foreign students by universities, especially economic criteria pertaining to profitability. This article examines the cases of two Québec universities. Both feature teaching exclusively in French, a minority language in North America. Based on existing literature, hypotheses concerning the impact of language and international networking on the recruitment of foreign students are tested. Analysis reveals that even if regular use of French is important for recruitment, it is not the only variable involved. The geographical and social context of each university also plays an important role, as does the networking activities of academics who build relationships based on cooperation with foreign institutions.
Number: 3
Keywords: Université de Montréal; Étudiants

Between the Future and the Present: Montreal University Student Youth and the Post-War Years, 1945-1960 - Hébert, Karine (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Université McGill; Université de Montréal; Étudiants

De Sainte-Croix à Maisonneuve : 75 ans d'histoire - Lachance, Laurent (Fides, 2003)
Keywords: Collèges classiques; Communautés religieuses; Congrégation de Sainte-Croix; Étudiants

Le Collège André-Grasset : 75 ans d'histoire - Bannon, Jacques (Fides, 2003)
Keywords: Collège André-Grasset; Collèges classiques; Communautés religieuses; Sulpiciens; Étudiants